Penerapan Filter Mahony Pada Tracking System Pergerakan Orientasi dan Posisi Kepala Berskala Ruang - Muhammad Kholash Fadhilah; Dahnial Syauqy; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Virtual Reality (VR) is a term in a 3D environment generated by a computer and has the ability to make users to be able to interact with alternative realities. To interact with virtual reality, users need devices that accommodate user interaction with the VR environment. A room scale VR device is capable of allowing users to interact more freely. VR devices that currently available in the market still require supporting external devices, resulting in a lack of device portability. Based on these problems, researchers developed a device based on head orientation and head position on a room scale. In the development of devices, testing is done to determine the performance of the device system. Testing of device systems involves the application of Mahony Filters as orientation filters. Tests are based on orientation data and position of user's head in a room. The testing of the device system obtains detection accuracy of head position data acquisition in a room area of ​​3.33m2 with an average deviation of 4.9cm from the range of actual space size and for the accuracy detection of orientation data by system, the average degree deviation is 2.59 degrees from the actual degree angle. In the classification of determining the heading by the system, that obtained success rate by 73.5%.